2021
DOI: 10.1186/s13244-021-01000-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic methods and therapeutic options of uveal melanoma with emphasis on MR imaging—Part I: MR imaging with pathologic correlation and technical considerations

Abstract: Uveal melanoma is a malignant neoplasm that derives from pigmented melanocytes of the uvea and involves, in order of decreasing prevalence, the choroid, ciliary body and iris. Its prognosis is related to histopathologic and genetic features, tumor size and location, extraocular extension. The diagnosis is fundamentally based on clinical evaluation (ophthalmoscopy, biomicroscopy) and ultrasonography. MRI is useful in case of untransparent lens or subretinal effusion. Moreover, MRI has a significant role to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 73 publications
0
43
0
Order By: Relevance
“…Imaging UM with MR requires a dedicated eye protocol consisting of 2D MS TSE sequences, which are indispensable for delineating tumor boundaries; 3D TSE sequences, which allow retrospective reformatting in all directions and 3D reconstructions, and are essential to assess tumor geometry and accurate measurements; and DWI and PWI sequences, which aid in the differential diagnosis, and potentially, provide prognostic information, predict treatment response, and permit earlier assessment of tumor response to radiotherapy than US [3,8,11,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging UM with MR requires a dedicated eye protocol consisting of 2D MS TSE sequences, which are indispensable for delineating tumor boundaries; 3D TSE sequences, which allow retrospective reformatting in all directions and 3D reconstructions, and are essential to assess tumor geometry and accurate measurements; and DWI and PWI sequences, which aid in the differential diagnosis, and potentially, provide prognostic information, predict treatment response, and permit earlier assessment of tumor response to radiotherapy than US [3,8,11,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the radiotherapy planning of UM with complex tumor shapes, such as some tumors with a mushroom configuration, is more difficult and deserves special attention [20]. The mushroom configuration is associated with breaks in Bruch's membrane [11,21]. Our study was consistent; we showed the importance of The amount of pigmentation in UM is variable, and although pronounced pigmentation has been associated with a less favorable prognosis [19], the accurate prognostic significance of pigmentation warrants further analysis [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma of the uveal tract is an uncommon malignancy, mainly affecting middleaged adult patients, primarily arising from the choroid and less frequently from the ciliary bodies and iris [1][2][3][4]. Uveal melanoma (UM), despite representing the most common primary intraocular malignant tumor of the adult age, is exceptionally unusual in the pediatric population in which it usually has congenital origin with poorer outcome and more frequent extraocular extension at the diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors that have historically been reported to be involved in the development of this neoplasm include: Fitzpatrick phototypes I-II, type 1 neurofibromatosis (NF-1), oculo-dermal melanocytosis (Ota nevus), dysplastic nevus syndrome, and choroidal nevi [5][6][7]. Although UM typically tends to remain asymptomatic for years before the diagnosis, a sudden retinal detachment often represents the presenting symptom of the tumor [1][2][3][4][5]. UM is a slow-growing tumor with indolent biological behavior but consistently poor prognosis, characterized by the development of liver metastases within 10-15 years after the diagnosis in about 50% of cases [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%